Improving the Ionic Conductivity of Carboxylated Nitrile Rubber/LDH Composites by Adding Imidazolium Bis(trifluoromethylsulfonyl)imide Ionic Liquids. Issue 1 (August 2014) - Laskowska, Anna; Marzec, Anna; Boiteux, Gisele; Zaborski, Marian; Gain, Olivier; Serghei, Anatoli; Maniukiewicz, Waldemar; Duchet‐Rumeau, Jannick; Gérard, Jean‐François; Galli, Giancarlo
Summary We investigated the ability of three imidazolium ionic liquids (ILs) (1‐ethyl‐3‐methylimidazolium bis(trifluoromethylsulfonyl)imide (EMIM TFSI), 1‐butyl‐3‐methylimidazolium bis(trifluoromethylsulfonyl)imide (BMIM TFSI), 1‐hexyl‐methylimidazolium bis(trifluoromethylsulfonyl)imide (HMIM TFSI)) that have the same anion but different alkyl chain lengths of cation in amounts of 2.5, 5, 10 and 15 phr (parts per hundred rubber)to improve the ionic conductivity of carboxylated nitrile butadiene rubber (XNBR)/layered double hydroxide (MgAl‐LDH) composites. The presence of these ionic liquids modified the relaxation behavior of the XNBR matrix. Increasing the length of the cation side‐chain (from ethyl‐ to hexyl‐) impactsthe glass transition temperature of the rubber matrix, the crosslink density, the mechanical properties and the ionic conductivity of the resulting XNBR/IL‐LDH composites. Among this group of ionic liquids, 1‐ethyl‐3‐methylimidazolium bis(trifluoromethylsulfonyl)imide (EMIM TFSI)or alternatively 1‐butyl‐3‐methylimidazolium bis(trifluoromethylsulfonyl)imide (BMIM TFSI)proved most suitable for enhancingthe ionic conductivity of rubber composites without substantial deterioration of their mechanical properties.